2015
DOI: 10.1016/j.foodres.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profiles and consumer acceptability of a range of sugar-reduced products on the UK market

Abstract: Current UK intake of non-milk extrinsic sugars (NMES) is above recommendations. Reducing the sugar content of processed high sugar foods through reformulation is one option for reducing consumption of NMES at a population level. However, reformulation can alter the sensory attributes of food products and influence consumer liking. This study evaluated consumer acceptance of a selection of products that are commercially-available in the UK; these included regular and sugar-reduced baked beans, strawberry jam, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 46 publications
1
51
1
Order By: Relevance
“…However, these samples were similar ( P > 0.05) to the prebiotic chocolate with sucrose (Sucro). Markey and others () studied the consumers’ acceptance of milk chocolate sweetened with maltitol as a sucrose replacer, and observed no differences in the flavor acceptance when compared to a traditional formulation (sucrose), with a lower acceptance for the attribute texture, differing from the findings of the present study.…”
Section: Resultscontrasting
confidence: 90%
“…However, these samples were similar ( P > 0.05) to the prebiotic chocolate with sucrose (Sucro). Markey and others () studied the consumers’ acceptance of milk chocolate sweetened with maltitol as a sucrose replacer, and observed no differences in the flavor acceptance when compared to a traditional formulation (sucrose), with a lower acceptance for the attribute texture, differing from the findings of the present study.…”
Section: Resultscontrasting
confidence: 90%
“…A previous cluster analysis of liquid dairy products highlighted that liking varied according to age, sex, and income (Richardson-Harman et al, 2000). Using a cluster approach, we have shown that a distinct cluster of consumers that were representative of the UK population with regard to age, sex, body mass index (BMI), and socioeconomic class (SEC) had less of a preference for a range of reformulated, sugarreduced products when compared with regular-sugar alternatives (Markey et al, 2015). To our knowledge, no study has used a cluster approach to investigate consumer acceptance of FA-modified dairy products and to examine whether consumer clusters of liking for such products are associated with sociodemographic characteristics.…”
Section: Introductionmentioning
confidence: 84%
“…As a result of time constraints, it was not feasible to assess the effect of information provision on acceptability of the milk and butter samples. In addition, not all of the product types were processed under standardized conditions (i.e., different process parameters and milk sources were used), and it is acknowledged that this could have affected product acceptance (Markey et al, 2015) independent of variations in FA or total fat content. Furthermore, it was not feasible to purchase all commercial samples in a single batch (cheese and butter or spread) or in units that were consistent with those of the modified and control dairy products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive consumption of sucrose is considered to be a major contributor in the progression of dental caries, metabolic diseases and hypertension . However, sucrose replacement by low‐calorie sweeteners could provide a feasible strategy for reduction of sugar intake . Thus the development of sugar‐reduced marmalades is an attractive alternative.…”
Section: Introductionmentioning
confidence: 99%